The Impact of Advanced Manufacturing Technology on Achieving Competitive Advantage: A Field Study at Foodstuff Manufactories in the Capital Municipality of Sana’a - Al-Ashwal, Ali Hussain Ali; Manaa, Osama Qaid Naji (University of Science and Technology Journal for Management and Human Sciences, 2024)
The study aimed to investigate the impact of advanced manufacturing technology on comparative advantage of foodstuff manufactories in the Capital Municipality of Sana’a. Using an analytical approach, data were collected from a sample of 90 employees through a questionnaire. The data were analyzed using inferential statistical methods applied with SPSS software. The findings revealed a positive influence of advanced manufacturing technology on the competitive advantage of foodstuff manufacturers in the Capital Municipality of Sana’a. The study also revealed that information technology dimension was the most influential factor affecting the competitive advantage of foodstuff manufactories, while the design and engineering dimension had the least impact. Based on these findings, the study recommends further strengthening the application of advanced manufacturing technology in foodstuff manufactories in the Capital Municipality of Sana’a. Additionally, it emphasizes the importance of robust supervision of the implemented manufacturing systems to ensure product quality. The study underscores the need for higher focus on the quality of raw materials used in the manufacturing process.